2020
DOI: 10.1063/5.0018235
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling approaches in laser-based material processing

Abstract: Predictive modeling represents an emerging field that combines existing and novel methodologies aimed to rapidly understand physical mechanisms and concurrently develop new materials, processes, and structures. In the current study, previously unexplored predictive modeling in a key-enabled technology, the laser-based manufacturing, aims to automate and forecast the effect of laser processing on material structures. The focus is centered on the performance of representative statistical and machine learning alg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Thus, although the control of coherent scattering effects is always the key to obtaining LIPSS of high regularity, the implementation of a general algorithm for controlling the regularity of LIPSS is still missing. Here, artificial intelligence and machine learning approaches [51] could contribute to improving LIPSS regularity in the future.…”
Section: Question 4 How Can the Regularity Of Lipss Be Controlled?mentioning
confidence: 99%
“…Thus, although the control of coherent scattering effects is always the key to obtaining LIPSS of high regularity, the implementation of a general algorithm for controlling the regularity of LIPSS is still missing. Here, artificial intelligence and machine learning approaches [51] could contribute to improving LIPSS regularity in the future.…”
Section: Question 4 How Can the Regularity Of Lipss Be Controlled?mentioning
confidence: 99%
“…Sohrabpoor et al [146] applied an ANN and adaptive inference model to predict the surface quality of laser-processed 316L stainless steel cylindrical pins when machined with a CO 2 laser. Velli et al [147] showed that the laser-induced periodic surface structures [148][149][150] produced via a Yb:KBW femtosecond source on stainless steel (and titanium alloy and crystalline silicon) could be predicted via a range of machine-learning models.…”
Section: Steelmentioning
confidence: 99%
“…Velli et al. [147] showed that the laser‐induced periodic surface structures [148–150] produced via a Yb:KBW femtosecond source on stainless steel (and titanium alloy and crystalline silicon) could be predicted via a range of machine‐learning models.…”
Section: Machine Learning and Laser Machiningmentioning
confidence: 99%
“…As mentioned above, the photosensitive performance of natural pigments has a wide distribution. Recently, machine learning methods in deep learning are widely utilized for training models of multicellular complexity, tissue specificity, biomedical design, protein structure, and chemical reaction. Recently, predictive modeling demonstrated a bright prospect in rapid clarification of the physical mechanisms of developing materials . Since the combination of parameters and the hidden mechanism and reactions affects the performance of our devices, an efficient numerical statistical and predictive analytical algorithm is necessary for the development of novel functional devices.…”
Section: Introductionmentioning
confidence: 99%
“…26−28 Recently, predictive modeling demonstrated a bright prospect in rapid clarification of the physical mechanisms of developing materials. 29 Since the combination of parameters and the hidden mechanism and reactions affects the performance of our devices, an efficient numerical statistical and predictive analytical algorithm is necessary for the development of novel functional devices. Thus, in this manuscript, we provide machine learning methods in deep learning which are worthy of mining natural pigments to investigate photosensitive performance.…”
Section: ■ Introductionmentioning
confidence: 99%